Comparison of hemostatic sealants on ovarian reserve during laparoscopic ovarian cystectomy. (November 2015) - Kang, Jun Hyeok; Kim, Yong Seok; Lee, San Hui; Kim, Woo Young
Abstract: Objective: To determine whether different methods of hemostasis and pathologic subtypes would lead to significant differences regarding ovarian reserve after laparoscopic ovarian cystectomy. Study design: Data were prospectively collected from 129 patients who underwent laparoscopic ovarian cystectomy with either a hemostatic sealant (FloSeal or TachoSil) or bipolar coagulation to achieve hemostasis. Serum anti-Müllerian hormone (AMH) levels as measured by enzyme immunoassay. Measurements were made preoperatively and at 3 months postsurgery in each group [bipolar coagulator group ( n  = 43), FloSeal group ( n  = 46), and TachoSil group ( n  = 40)]. Results: Age, BMI, parity, sociodemographic variables, and preoperative AMH levels were similar between the three groups of patients. At 3 months post-surgery, the AMH decline rate was significantly greater in the bipolar coagulation group compared with the two hemostatic sealant groups (41.2% [IQR, 16.7–52.4] vs. 15.4% [IQR, 5.2–41.9], respectively; P  = 0.003). However, the AMH decline rates of the two hemostatic sealant groups (FloSeal and TachoSil) were not significantly different (15.4% [IQR, 7.8–44.6] vs. 15.9% [IQR, 0.7–41.1], P  = 0.962). Also, subgroup analysis according to ovarian cyst type revealed no significant differences in the rate of serum AMH decline regardless of the hemostatic method (bipolar group, P  = 0.30; FloSeal group, P  = 0.47, and TachoSil group, P  = 0.79). Conclusion: The two hemostatic sealants (FloSeal and Tachosil) did not exhibit any significant differences regarding the preservation of ovarian reserve regardless of ovarian cyst type.